Reset [videorecording (DVD)] - Bae, Min; Moon, Jongteak; Park, Young Dae (Freestyle Digital Media, 2023)
Min Bae investigates the momentous sinking of the Sewol Ferry off the coast of South Korea. The film will communicate that this was not a typical accident, but something that could have been prevented.